PERANAN KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH EFEKTIF DI SMA NEGERI KOTA PADANG - SUMATERA BARAT - Ristapawa Indra; Risdaneti Risdaneti (STKIP Pesisir Selatan, 2016)
effective schools. Professional school leadership to contribute to the realization of 11 characteristics of effective schools in SMA Negeri Padang City as much as 58.5 The purpose of this study was to evaluate the stage of effective school performance based on 11 characteristics of effective schools by Mortimore (1995) as well as to evaluate the level of correlation between individual characteristics of effective school leadership and contribution to the school principals effectively. The research sample set of 16 schools with a number of leaders of 60 people and the number of teachers as many as 105 people. Determination of the number of teachers as much as seven to 10 people for each school selected based on the views Halphin (1957). Diperolehi quantitative data through a set of instruments on characteristics of effective schools by 11 Mortimore (1995). Data were analyzed descriptively using frequency, min score, percentage and standard deviation and inferential statistics (Pearson correlation, simple linear regression). The findings show stage school performance effectively SMA keseluruan Padang City in the view of principals and teachers are at a very high stage. There is a significant correlation between the stage of high school leadership professional with the realization of 11 overall characteristics of % and the other percentage contributed by other variabel s that are not involved in this study. School leadership is an important faktor for the realization of 11 characteristics of effective schools in SMA Negeri Padang.